Identifying and prioritising epilepsy treatment uncertainties. Issue 8 (18th June 2010) - Thomas, R H; Hammond, C L; Bodger, O G; Rees, M I; Smith, P E M
Abstract : Objective: To identify and prioritise uncertainties regarding epilepsy treatment from people with epilepsy, their carers and epilepsy clinicians. Background: Failure to acknowledge and address genuine treatment uncertainties has caused unnecessary iatrogenic harm. The authors define an uncertainty as a question that cannot be sufficiently answered by a systematic review of the literature. The database of the uncertainties of the effects of treatment (DUETs) is a collection of 'known unknowns' that enables patient-prioritised research. Design and participants: The authors organised five separate focus groups (two consisting of clinicians, three of patients and carers) to garner questions on epilepsy treatment uncertainties; these yielded 398 potential research questions. Participants were asked to rank the questions in terms of importance. The authors then performed a thematic analysis. Results: Patients rated questions concerning cognitive drug side effects, managing the consequences of side effects and improving public awareness about the treatment of epilepsy through improved services as most important. For clinicians, the most important themes were treatment programmes for non-epileptic attack disorder (NEAD), concerns about side effects in utero and uncertainties regarding prescribing in pregnancy. Conclusions: Patient uncertainties were often focussed on very practical considerations—how to take prescribed medication, access to services and how to minimise drug side effects. Clinicians' questions were also practical but clustered around 'the challenging consultation'—for example, NEAD, sudden unexplained death in epilepsy and prescribing in pregnancy. The authors have published the research questions on NHS Evidence and are working with them to identify those questions which represent genuine uncertainties. The authors encourage other clinicians to seek patient and carers' priorities in order to shape their research agenda.